Penguatan Kecerdasan Sikap Multikultural (Sosiologis) - Kusmiran; Amril M (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
The purpose of this study was to analyze the strengthening of multicultural (sociological) attitude intelligence. The research method in this paper uses qualitative research methods. The results of this study are forms of strengthening multicultural attitude intelligence consisting of: 1) democratic attitudes, 2) Pluralism attitudes, 3) Humanism attitudes, and 4) tolerance attitudes, while forms of strengthening intelligence are 1) multicultural attitudes, 2) pluralism attitudes and 3) attitude of humanism